From Wall Street to main street - Lee, Chulho Christopher (Economic and business review, 2026)
This study examines the relationship between hospital financial performance and operational efficiency. Using data from the American Hospital Association (AHA), we find that profitability, debt coverage, and working capital efficiency are positively associated with hospital efficiency, while liquidity and capital structure exhibit a negative correlation. Fixed-asset efficiency, however, shows no significant impact on hospital operational efficiency. Furthermore, we find that the operational efficiency of urban hospitals is, in general, more sensitive to financial performance than that of rural hospitals. These findings provide practical insights for healthcare administrators and policymakers aiming to enhance hospital operational efficiency and promote equitable care delivery.
Keywords: bolnišnice; business efficiency; hospitals; management; uspešnost poslovanja